Electron-Correlation-Induced Charge Density Wave in FeGe - Wu, Lin; Hu, Yating; Fan, Dongze; Wang, Di; Wan, Xiangang (Chinese physics letters, 2023)
As the first magnetic kagome material to exhibit the charge density wave (CDW) order, FeGe has attracted much attention in recent research. Similar to A V 3 Sb 5 ( A = K, Cs, Rb), FeGe exhibits the CDW pattern with an in-plane 2×2 structure and the existence of van Hove singularities near the Fermi level. However, sharply different from A V 3 Sb 5 which has phonon instability at M point, all the theoretically calculated phonon frequencies in FeGe remain positive. Based on first-principles calculations, we surprisingly find that the maximum of nesting function is at K point instead of M point. Two Fermi pockets with Fe- d xz and Fe- d x 2 – y 2 / d xy orbital characters have large contribution to the Fermi nesting, which evolve significantly with k z , indicating the highly three-dimensional (3D) feature of FeGe in contrast to A V 3 Sb 5 . Considering the effect of local Coulomb interaction, we reveal that the instability at K point is significantly suppressed due to the sublattice interference mechanism. Meanwhile, the wave functions nested by vector M have many ingredients located at the same Fe site, thus the instability at M point is enhanced. This indicates that the electron correlation, rather than electron-phonon interaction, plays a key role in the CDW transition at M point.